High‐Performance Photodetector and Angular‐Dependent Random Lasing from Long‐Chain Organic Diammonium Sandwiched 2D Hybrid Perovskite Non‐Linear Optical Single Crystal. (7th February 2023) - Ulaganathan, Rajesh Kumar; Roy, Pradip Kumar; Mhatre, Swapnil Milind; Murugesan, Raghavan Chinnambedu; Chen, Wei‐Liang; Lai, Man‐Hong; Subramanian, Ambika; Lin, Chang‐Yu; Chang, Yu‐Ming; Canulescu, Stela; Rozhin, Alex; Liang, Chi‐Te; et al.
Abstract: 3D organic‐inorganic metal halide perovskites are excellent materials for optoelectronic applications due to their exceptional properties, solution processability, and cost‐effectiveness. However, the lack of environmental stability highly restricts them from practical applications. Herein, a stable centimeter‐long 2D hybrid perovskite (N‐MPDA)[PbBr4 ] single crystal using divalent N1‐methylpropane‐1, 3‐diammonium (N‐MPDA) cation as an organic spacer, is reported. The as‐grown single crystal exhibits stable optoelectronic performance, low threshold random lasing, and multi‐photon luminescence/multi‐harmonic generation. A photoconductive device fabricated using (N‐MPDA)[PbBr4 ] single crystal exhibits an excellent photoresponsivity (≈124 AW −1 at 405 nm) that is ≈4 orders of magnitudes higher than that of monovalent organic spacer‐assisted 2D perovskites, such as (BA)2 PbBr4 and (PEA)2 PbBr4, and large specific detectivity (≈10 12 Jones). As an optical gain media, the (N‐MPDA)[PbBr4 ] single crystal exhibits a low threshold random lasing (≈6.5 µJ cm −2 ) with angular dependent narrow linewidth (≈0.1 nm) and high‐quality factor ( Q ≈ 2673). Based on these results, the outstanding optoelectronic merits of (N‐MPDA)[PbBr4 ] single crystal will offer a high‐performance device and act as a dynamic material to construct stable future electronics and optoelectronic‐based applications. Abstract : Asymmetric diammonium di‐cation assisted nonlinear optical 2D (N‐MPDA)[PbBr4 ] hybrid perovskite single crystal shows a stable photodetector performance with high responsivity, large specific detectivity, and functions as an optical gain medial for random lasing with high "Q" factor. The above features promising the asymmetric diammonium spacer will be highly beneficial in advancing 2D perovskite materials for steady optoelectronic applications.